MXene auxiliary cation exchange membrane for electrodialysis desalination and preparation method of MXene auxiliary cation exchange membrane
By adding ultrasonic MXene nanosheets to the sulfonated polymer, an efficient ion transport channel is constructed, which solves the problem of insufficient performance of existing ion exchange membranes in electrodialysis desalination, and achieves efficient electrodialysis desalination performance and stability simplifies the preparation process and reduces costs.
Patent Information
- Application Number
- CN202411421891.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-20
AI Technical Summary
The existing high sulfonation ion exchange membrane has poor mechanical stability due to high water absorption, while the low sulfonation film has low ion exchange capacity, resulting in poor performance in applications such as electrodialysis and desalination, and nanomaterials in composite membranes. The sheet size impact is underutilized, the preparation process is complex and costly.
MXene nanosheets of different sheet sizes were obtained by sonication and simply blended into sulfonated polymers to construct a composite cation exchange membrane with high ion conductivity, and use the unique properties of MXene to form a hydrogen bond network and continuous ions. Transmission channel to improve the transmission efficiency of ions.
It achieves high ionic conductivity and excellent electrodialysis desalination performance, reduces preparation complexity and cost, improves the chemical and mechanical stability of the membrane, and is suitable for a variety of liquid flow battery systems.
Smart Images

Figure CN119170840A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of cation exchange membrane batteries, and in particular, relates to a MXene-assisted cation exchange membrane for electrodialysis desalination and a preparation method thereof. Background Art
[0002] Ion exchange membranes (IEMs) have attracted great interest in both academia and industry due to their potential applications in electromembrane processes, including: (1) water purification, such as electrodialysis desalination, capacitive deionization by membrane, and diffusion dialysis; (2) energy production; (3) energy storage; and (4) chlor-alkali processes.
[0003] The best way to improve the ion exchangeability of polymer membranes is to introduce a certain amount of acidic groups, such as -SO3H groups, along the polymer backbone through a sulfonation reaction. These charged groups fixed to the polymer backbone can partially or completely prevent ions with the same charge from passing through the membrane, thereby selectively permeating cations. However, ion exchange membranes with a high degree of sulfonation inevitably lead to high water absorption, which may cause the membrane to swell or even dissolve, thereby reducing the dimensional / mechanical stability of the membrane, which greatly limits their use. Ion exchange membranes with a low degree of sulfonation usually have high membrane surface resistance due to their low ion exchange capacity, resulting in poor ion exchange capacity. Therefore, it is crucial to develop IEMs with ideal electrochemical and physicochemical properties for efficient production of fresh water. Explorations for the development of IEMs with excellent performance are ongoing, among which the incorporation of nanomaterials (NMs) is also being studied as a means of improving their performance. Mixing nanomaterials into IEMs can improve their performance through the complementary and synergistic effects between nanomaterials and base membranes. This can greatly improve the applicability of polymers as IEMs.
[0004] Since MXenes (titanium carbide (Ti3C2Tx)) were first produced by researchers at Drexel University in 2011, they have become a new and attractive nanomaterial due to their unique properties, including excellent stability, large specific surface area, high electrical / thermal conductivity, excellent oxidation resistance and hydrophilicity. The Chinese invention patent application number 201510997500.1 discloses an organic-inorganic hybrid proton exchange membrane prepared by blending Nafion and a two-dimensional material (MXene). However, nanosheet size, as a key factor affecting the performance of two-dimensional materials, has not received significant attention in the research on the preparation of composite membranes.
[0005] CN117497813A discloses a preparation method of a SPEEK / MXene composite ion exchange membrane, including: preparing MXene by acid etching; MXene cation intercalation and surface modification to obtain two-dimensional transition metal carbon / nitride MXene; preparing dry flocculent SPEEK; adding two-dimensional transition metal carbon / nitride MXene to a high boiling point organic solvent and peeling it into a single-layer structure; dissolving SPEEK in an organic solution of MXene and stirring it evenly; casting into a film, heating and drying, cooling, and obtaining a SPEEK / MXene substrate membrane; pouring an organic solution of MXene onto the surface of the SPEEK / MXene substrate membrane, standing, heating and drying, and cooling, and obtaining. The composite ion exchange membrane prepared by the present invention has excellent ion selectivity and ion conductivity, good chemical stability and mechanical properties, is suitable for a variety of liquid flow battery systems, and has good battery performance.
[0006] CN117004222A discloses a modified MXene-sulfonated polysulfone composite material and its preparation method and application. The modified MXene-sulfonated polysulfone composite material comprises sulfonated polysulfone, and a proton acid-modified MXene assembled on the sulfonated polysulfone molecule through intermolecular hydrogen bonds; wherein the proton acid is a proton acid containing a sulfonic acid group or a carboxyl group. The modified MXene-sulfonated polysulfone composite material provided by the present invention has high proton conductivity, low fuel permeability and excellent stability, a proton exchange capacity of more than 1.0 mmol / g, a proton conductivity of more than 0.078 S / cm, and a methanol permeability of 9.4×10 -7 cm 2 ·s -1 The following has broad application prospects in the field of proton exchange membrane fuel cells.
[0007] In summary, the above methods mainly modify MXene before further research, which makes the preparation process more complicated and costly. Summary of the invention
[0008] The purpose of the present invention is to prepare an organic-inorganic composite ion exchange membrane from the perspective of nanosheet size in view of the above-mentioned existing problems. This method can obtain MXene of different sheet sizes by simple ultrasonic treatment, and then incorporate the small sheet MXene into the sulfonated polymer through a simple blending process, and finally obtain a composite ion exchange membrane with high ion conductivity by means of the ion transmission channel constructed by MXene. Compared with the existing method of modifying MXene and then treating it, it is more efficient and has a certain effect on ion transmission.
[0009] To achieve the above object, the present invention adopts the following technical solution:
[0010] A MXene-assisted cation exchange membrane for electrodialysis desalination, wherein the MXene-assisted cation exchange membrane for electrodialysis desalination comprises a matrix formed by a sulfonated polymer and MXene nanosheets filled in the matrix.
[0011] Furthermore, the mass ratio of the sulfonated polymer to the Mxene nanosheet is 10-15:0.1-0.4.
[0012] Furthermore, the MXene nanosheet is a MXene two-dimensional nanosheet with a small sheet size, and the MXene two-dimensional nanosheet is a single sheet with a size of 0.5-8 μm.
[0013] Furthermore, the sulfonated polymer is one of sulfonated polyethersulfone, sulfonated polysulfone or sulfonated polyetheretherketone.
[0014] Furthermore, the ion exchange capacity of the MXene-assisted cation exchange membrane for electrodialysis desalination is 0.81-0.865 mmol / g, and the electrodialysis desalination performance is 85-89.5%.
[0015] The present invention also provides a method for preparing the MXene-assisted cation exchange membrane for electrodialysis desalination, wherein the preparation method comprises the following steps:
[0016] S1. Synthesis of MXene powder
[0017] S1.1, gradually add Ti3AlC2 into the mixture of LiF and HCl, heat and stir to react;
[0018] S1.2. After the reaction, wash with deionized water and ethanol several times, and then freeze-dry to obtain MXene powder;
[0019] S2. Preparation of MXene-assisted cation exchange membrane
[0020] S2.1, placing a sulfonated polymer and an organic solvent in a container, stirring under heating conditions, to obtain a sulfonated polymer solution;
[0021] S2.2, adding MXene powder into a container containing an organic solvent and subjecting it to ultrasonic treatment to obtain a dispersion of MXene nanosheets;
[0022] S2.3. Stir the MXene nanosheet dispersion and the sulfonated polymer solution under heating conditions to obtain a casting solution; then cast the obtained casting solution onto a glass plate, and after drying, obtain the MXene-assisted cation exchange membrane for electrodialysis desalination, which is placed in deionized water for standby use.
[0023] Furthermore, in step S1.1, the mass of the Ti3AlC2 is 7 g, the volume of the HCI is 100 mL, the concentration is 7 mol / L, and the mass of the LiF is 4 g.
[0024] Furthermore, in step S1.1, the heating temperature is 80° C. and the heating time is 40 h.
[0025] Furthermore, in step 2.1, the mass volume ratio of the sulfonated polymer to the organic solvent is 10-15 g: 35-40 mL; in step 2.2, the mass volume ratio of the MXene powder to the organic solvent is 0.1-0.4 g: 50 mL; the organic solvent is one of N-methylpyrrolidone, dimethyl sulfoxide, dimethylacetamide, dimethylformamide, 1,4-dioxane, chloroform, and dichloromethane, or a mixture of any two thereof.
[0026] Furthermore, in step 2.2, the ultrasonic treatment time is 0.5-3h; in step 2.1, the heating is heating at 65-85°C and 300-500rpm for 5h; in step 2.3, the heating is heating at 50-80°C and 200-450rpm for 10-20h.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] (1) In the MXene-assisted cation exchange membrane prepared by the present invention, the MXene nanosheets filled in the matrix have unique properties, including excellent stability, large specific surface area, high electrical / thermal conductivity, excellent oxidation resistance and hydrophilicity. Therefore, MXene can form a wide range of hydrogen bond networks in the polymer membrane and help promote the transport of ions;
[0029] (2) In the past, composite ion exchange membranes prepared by adjusting the content of fillers had a limited degree of adjustment, and the increase of fillers could easily cause agglomeration. The MXene-assisted cation exchange membrane prepared by the present invention is based on the sheet size. MXene with a small sheet size is added to the matrix formed by the sulfonated polymer, which not only increases the dispersibility in the matrix, but also constructs a more continuous ion transmission channel in the matrix, which is beneficial to the further transmission of ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a cross-sectional SEM image of the composite ion exchange membrane in Example 1;
[0031] Figure 2 is the AFM image of the MXene nanosheet in Example 1;
[0032] Figure 3 The desalination effect of the composite ion exchange membrane in the electrodialysis desalination process in Example 1;
[0033] Figure 4 is a SEM image of the cross section of the sulfonated polymer membrane in Comparative Example 1;
[0034] Figure 5 This is the AFM image of the MXene nanosheets in Comparative Example 2. DETAILED DESCRIPTION
[0035] The following are specific embodiments of the present invention, and the embodiments are intended to further describe the present invention rather than to limit the present invention.
[0036] Example 1
[0037] S1. Synthesis of Mxene powder
[0038] S1.1, gradually add 7g Ti3AlC2 into a mixture of 100mL HCl (7mol / L) and LiF (4g), and then stir the reaction at 80℃ for 40h;
[0039] S1.2. After the reaction, wash with deionized water and ethanol several times. Finally, MXene powder is obtained by freeze drying. S2. Preparation of MXene-assisted cation exchange membrane
[0040] S2.1, place 10 g of sulfonated polysulfone and 40 mL of dimethylacetamide in a round-bottom flask, and heat at 85°C and 500 rpm for 5 h to form a homogeneous solution, i.e., the sulfonated polymer solution;
[0041] S2.2, dissolving 0.2 g of MXene powder in 50 mL of dimethylacetamide and ultrasonically treating for 2 h to obtain a dispersion of MXene nanosheets;
[0042] S2.3. Heat the obtained Mxene nanosheet dispersion and sulfonated polymer solution at 60°C and 400 rpm for 10 h, then let it stand at a constant temperature for degassing, place it on a clean glass plate, use a metal scraper to spread it into a primary film, place the primary film in a 65°C oven for 12 h to form a film, and then place it in deionized water.
[0043] The MXene nanosheet dispersion prepared by the above step S2.2 was tested by AFM and its sheet size was 2 μm.
[0044] The cross-sectional SEM image of the prepared ion exchange membrane is shown in Figure 1 As shown;
[0045] The AFM images of the prepared MXene nanosheets are shown in Figure 2 shown; through Figure 2The AFM image shows the size of the MXene flakes.
[0046] The desalination effect of the prepared ion exchange membrane in the electrodialysis desalination process is as follows Figure 3 shown; through Figure 3 It can be seen that adding small sheets of MXene to the sulfonated polymer can achieve excellent desalination effect.
[0047] The ion exchange capacity of the prepared ion exchange membrane is 0.865 mmol / g, and the NaCl removal rate during the electrodialysis process is 89.5%.
[0048] Example 2
[0049] S1. Synthesis of Mxene powder
[0050] The preparation method of MXene powder is the same as that in Example 1.
[0051] S2. Preparation of MXene-assisted cation exchange membrane
[0052] S2.1, place 15 g of sulfonated polysulfone and 35 mL of dimethylformamide in a round-bottom flask, and heat at 85°C and 500 rpm for 5 h to form a homogeneous solution, i.e., the sulfonated polymer solution;
[0053] S2.2, dissolving 0.2 g of MXene powder in 50 mL of dimethylformamide and ultrasonically treating for 3 h to obtain a dispersion of MXene nanosheets;
[0054] S2.3. Heat the obtained Mxene nanosheet dispersion and sulfonated polymer solution at 80°C and 200 rpm for 15 h, then let it stand at a constant temperature for degassing, place it on a clean glass plate, use a metal scraper to spread it into a primary film, place the primary film in a 65°C oven for 12 h to form a film, and then place it in deionized water.
[0055] The MXene nanosheet dispersion prepared by the above step S2.2 was tested by AFM and its sheet size was 1 μm.
[0056] The ion exchange capacity of the prepared ion exchange membrane is 0.85 mmol / g, and the NaCl removal rate during the electrodialysis process is 88.5%.
[0057] Example 3
[0058] S1. Synthesis of Mxene powder
[0059] The preparation method of MXene powder is the same as that in Example 1.
[0060] S2. Preparation of MXene-assisted cation exchange membrane
[0061] S2.1, place 10 g of sulfonated polysulfone and 40 mL of dimethylformamide in a round-bottom flask, and heat at 85°C and 500 rpm for 5 h to form a homogeneous solution, i.e., the sulfonated polymer solution;
[0062] S2.2, dissolving 0.1 g MXene powder in 50 mL dimethylformamide and ultrasonically treating for 2 h to obtain a dispersion of MXene nanosheets;
[0063] S2.3. Heat the obtained Mxene nanosheet dispersion and sulfonated polymer solution at 60°C and 400 rpm for 10 h, then let it stand at a constant temperature for degassing, place it on a clean glass plate, use a metal scraper to spread it into a primary film, place the primary film in a 65°C oven for 12 h to form a film, and then place it in deionized water.
[0064] The MXene nanosheet dispersion prepared by the above step S2.2 was tested by AFM and its sheet size was 2 μm.
[0065] The ion exchange capacity of the prepared ion exchange membrane is 0.86 mmol / g, and the NaCl removal rate during the electrodialysis process is 89%.
[0066] Example 4
[0067] S1. Synthesis of Mxene powder
[0068] The preparation method of MXene powder is the same as that in Example 1.
[0069] S2. Preparation of MXene-assisted cation exchange membrane
[0070] S2.1, place 15 g of sulfonated polysulfone and 35 mL of dimethylacetamide in a round-bottom flask, and heat at 85°C and 300 rpm for 5 h to form a homogeneous solution, i.e., the sulfonated polymer solution;
[0071] S2.2, dissolving 0.4 g MXene powder in 50 mL dimethylacetamide and ultrasonically treating for 0.5 h to obtain a dispersion of MXene nanosheets;
[0072] S2.3. Heat the obtained Mxene nanosheet dispersion and sulfonated polymer solution at 50°C and 450 rpm for 20 h, then let it stand at a constant temperature for degassing, place it on a clean glass plate, use a metal scraper to spread it into a primary film, place the primary film in a 65°C oven for 12 h to form a film, and then place it in deionized water.
[0073] The MXene nanosheet dispersion prepared by the above step S2.2 was tested by AFM and its sheet size was 8μm.
[0074] The ion exchange capacity of the prepared ion exchange membrane is 0.81 mmol / g, and the NaCl removal rate during the electrodialysis process is 85%.
[0075] Example 5
[0076] S1. Synthesis of Mxene powder
[0077] The preparation method of MXene powder is the same as that in Example 1.
[0078] S2. Preparation of MXene-assisted cation exchange membrane
[0079] S2.1, place 10 g of sulfonated polysulfone and 40 mL of N-methylpyrrolidone in a round-bottom flask, and heat at 65°C and 500 rpm for 5 h to form a homogeneous solution, i.e., the sulfonated polymer solution;
[0080] S2.2, dissolving 0.2 g of MXene powder in 50 mL of N-methylpyrrolidone and ultrasonically treating for 0.5 h to obtain a dispersion of MXene nanosheets;
[0081] S2.3. Heat the obtained Mxene nanosheet dispersion and sulfonated polymer solution at 70°C and 300 rpm for 10 h, then let it stand at a constant temperature for degassing, place it on a clean glass plate, use a metal scraper to spread it into a primary film, place the primary film in a 65°C oven for 12 h to form a film, and then place it in deionized water.
[0082] The MXene nanosheet dispersion prepared by the above step S2.2 was tested by AFM and its sheet size was 8μm.
[0083] The ion exchange capacity of the prepared ion exchange membrane is 0.83 mmol / g, and the NaCl removal rate during the electrodialysis process is 86%.
[0084] Comparative Example 1
[0085] 10 g of sulfonated polysulfone and 90 mL of dimethylformamide were placed in a round-bottom flask, heated at 85°C and 500 rpm for 15 h to form a homogeneous solution, then allowed to stand at a constant temperature for degassing, placed on a clean glass plate, and spread into a primary membrane using a metal scraper. The primary membrane was placed in an oven at 65°C for 12 h to form a sulfonated polymer membrane, which was then placed in deionized water.
[0086] The cross-sectional SEM image of the prepared sulfonated polymer membrane is shown in Figure 4 By Figure 4 and Figure 1 By comparison, we can observe the effect of the addition of MXene on the micromorphology of the composite film. The original film is smoother and denser, while the composite film shows an irregular morphology after the addition of MXene.
[0087] The ion exchange capacity of the prepared sulfonated polymer membrane is 0.81 mmol / g, and the NaCl removal rate during the electrodialysis process is 84%.
[0088] Comparative Example 2
[0089] S1. Synthesis of Mxene powder
[0090] The preparation method of MXene powder is the same as that in Example 1.
[0091] S2. Preparation of MXene-assisted cation exchange membrane
[0092] S2.1, place 10 g of sulfonated polysulfone and 40 mL of dimethylacetamide in a round-bottom flask, and heat at 85°C and 500 rpm for 5 h to form a homogeneous solution, i.e., the sulfonated polymer solution;
[0093] S2.2. Heat 0.4 g of MXene powder and sulfonated polymer solution at 60 °C and 500 rpm for 10 h, then let it stand at a constant temperature for degassing, place it on a clean glass plate, use a metal scraper to spread it into a primary film, place the primary film in a 65 °C oven for 12 h to form a film, and then place it in deionized water.
[0094] The MXene powder synthesized in step S1 was tested by AFM and its flake size was found to be 8.5 μm.
[0095] The AFM images of the prepared MXene nanosheets are shown in Figure 5 As shown;
[0096] The ion exchange capacity of the prepared ion exchange membrane is 0.805 mmol / g, and the NaCl removal rate during the electrodialysis process is 84.5%.
Claims
1. A MXene-assisted cation exchange membrane for electrodialysis desalination, characterized in that: The MXene-assisted cation exchange membrane for electrodialysis desalination comprises a matrix formed by a sulfonated polymer and MXene nanosheets filled in the matrix.
2. The MXene-assisted cation exchange membrane for electrodialysis desalination according to claim 1, characterized in that: The mass ratio of the sulfonated polymer to the Mxene nanosheet is 10-15:0.1-0.
4.
3. The MXene-assisted cation exchange membrane for electrodialysis desalination according to claim 2, characterized in that: The MXene nanosheet is a MXene two-dimensional nanosheet with a small sheet size. The MXene two-dimensional nanosheet is a single sheet with a size of 0.5-8 μm.
4. The MXene-assisted cation exchange membrane for electrodialysis desalination according to claim 3, characterized in that: The sulfonated polymer is one of sulfonated polyether sulfone, sulfonated polysulfone or sulfonated polyether ether ketone.
5. The MXene-assisted cation exchange membrane for electrodialysis desalination according to any one of claims 1 to 4, characterized in that: The ion exchange capacity of the MXene-assisted cation exchange membrane for electrodialysis desalination is 0.81-0.865 mmol / g, and the electrodialysis desalination performance is 85-89.5%.
6. A method for preparing a MXene-assisted cation exchange membrane for electrodialysis desalination according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1. Synthesis of MXene powder S1.1, gradually add Ti3AlC2 into the mixture of LiF and HCl, heat and stir to react; S1.
2. After the reaction, wash with deionized water and ethanol several times, and then freeze-dry to obtain MXene powder; S2. Preparation of MXene-assisted cation exchange membrane S2.1, placing a sulfonated polymer and an organic solvent in a container, stirring under heating conditions, to obtain a sulfonated polymer solution; S2.2, adding MXene powder into a container containing an organic solvent and ultrasonically treating it to obtain a dispersion of MXene nanosheets; S2.
3. Stir the MXene nanosheet dispersion and the sulfonated polymer solution under heating conditions to obtain a casting solution; then cast the obtained casting solution onto a glass plate, and after drying, obtain the MXene-assisted cation exchange membrane for electrodialysis desalination, which is placed in deionized water for standby use.
7. The preparation method according to claim 6, characterized in that: In step S1.1, the mass of the Ti3AlC2 is 7 g, the volume of the HCI is 100 mL, the concentration is 7 mol / L, and the mass of the LiF is 4 g.
8. The preparation method according to claim 6 or 7, characterized in that: In step S1.1, the heating temperature is 80° C. and the heating time is 40 h.
9. The preparation method according to claim 6, characterized in that: In step 2.1, the mass volume ratio of the sulfonated polymer to the organic solvent is 10-15 g: 35-40 mL; in step 2.2, the mass volume ratio of the MXene powder to the organic solvent is 0.1-0.4 g: 50 mL; the organic solvent is one of N-methylpyrrolidone, dimethyl sulfoxide, dimethylacetamide, dimethylformamide, 1,4-dioxane, chloroform, and dichloromethane, or a mixture of any two thereof.
10. The preparation method according to claim 6, characterized in that: In step 2.2, the ultrasonic treatment time is 0.5-3h; in step 2.1, the heating is heating at 65-85°C and 300-500rpm for 5h; in step 2.3, the heating is heating at 50-80°C and 200-450rpm for 10-20h.
Citation Information
Patent Citations
Organic-inorganic hybrid proton exchange membrane and preparation method and application thereof
CN105576267A
Modified MXene-sulfonated polysulfone composite material as well as preparation method and application thereof
CN117004222A
Preparation method of SPEEK / MXene composite ion exchange membrane
CN117497813A
Cited By
Proton exchange membrane and preparation method and application thereof
CN120473534A
Functionalized few-layer MXene, preparation method and high-conductivity proton exchange membrane
CN120483158A
